HUBUNGAN LINGKAR LEHER DENGAN OBESITAS PADA MAHASISWA FAKULTAS KEDOKTERAN UNIVERSITAS SAM RATULANGI - Laoh, Veronica C. E. (Universitas Sam Ratulangi, 2013)
Abstract: Background. Obesity is the factors that make another disease happen, especially degenerative diseases, Many Anthropometrical methods are used to categorized obesity, and among them which commonly used is body mass index, eventually the limitation of body mass index is not accurately in special condition. Neck circle is an alternative method that easy to understand like body mass index because neck circle always related with other degenerative diseases. Purpose: The purpose of this study is to know the relationship between the length of neck circle with obesity in students in Medical Faculty of Sam Ratulangi University. Methods: This Observational study using cross sectional design which will be realized on November 2012 in Medical Faculty of Sam Ratulangi University. The measuring do with the way that want to know the relationship between obesity body mass index with special provisions, and the measurement of neck circle length used measuring tape onemed, and analysis used Spearman correlation experiment test. Results. 111 respondents getting obesity, 73 men with r = 0,561 and p=0,000 and 38 women with r = 0,824 and p = 0,000. It means having strong relationship between to each research subject. Conclusion: There is strong relationship between neck circle length and subject that getting obesity according to 73 men and 38 women in Medical Faculty of Sam Ratulangi University Students. Key Words. Obesity, neck circle length, body mass index, degenerative diseases. Abstrak: Obesitas merupakan faktor resiko terjadi berbagai macam penyakit termasuk penyakit degeneratif, Berbagai cara antropometri digunakan untuk menentukan obesitas dan yang tersering digunakan yaitu indeks massa tubuh namun keterbatasannya ialah tidak akurat pada kondisi tertentu. Lingkar leher merupakan metode alternatif yang muda seperti indeks massa tubuh dikarenakan lingkar leher sering dikaitkan dengan beberapa penyakit degeneratif. Tujuan: Penelitian ini bertujuan untuk mengetahui hubungan antara lingkar leher dengan obesitas pada mahasiswa Fakultas Kedokteran Universitas Sam Ratulangi. Metode: Penelitian observasional dengan desain cross sectional dilaksanakan pada bulan November tahun 2012 di Fakultas Kedokteran Universitas Sam Ratulangi. Pengukuran dilakukan dengan cara mengetahui obesitas dengan metode indeks massa tubuh dengan syarat tertentu dan pemeriksaan lingkar leher dengan menggunakan pita ukur OneMed, analisis menggunakan uji korelasi spearman. Hasil: Sebanyak 111 responden yang mengalami obesitas, pada laki-laki berjumlah 73 orang dengan nilai r = 0,561 dan p sebesar 0,000 dan pada perempuan berjumlah 38 orang dengan nilai r = 824 dan p sebesar 0,000 yang berarti memiliki hubungan yang kuat pada masing-masing subjek penelitian. Simpulan: Terdapat hubungan antara lingkar leher dan subjek yang mengalami obesitas pada laki-laki yang berjumlah 73 orang dan perempuan yang berjumlah 38 orang dengan jumlah keseluruhan yaitu 111 orang pada mahasiswa Fakultas Kedokteran Universitas Sam Ratulangi. Kata kunci: Obesitas, lingkar leher, indeks massa tubuh, penyakit degeneratif.